2018
DOI: 10.1021/acs.est.7b05062
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Titanium Dioxide (nTiO2) Transport in Natural Sediments: Importance of Soil Organic Matter and Fe/Al Oxyhydroxides

Abstract: Many engineered nanoparticle (ENP) transport experiments use quartz sand as the transport media; however, sediments are complex in nature, with heterogeneous compositions that may influence transport. Nanoscale titanium dioxide (nTiO) transport in water-saturated columns of quartz sand and variations of a natural sediment was studied, with the objective of understanding the influence of soil organic matter (SOM) and Fe/Al-oxyhydroxides and identifying the underlying mechanisms. Results indicated nTiO transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…The increase in Al, Fe and Si atoms in the sediment particles means that these elements are released from the organic matter under the freeze-thaw action, and the increase in oxygen consumption during the release process leads to a decrease in the O atom content. This result confirms the hypothesis presented by Leanne et al [33] that freeze-thaw cycles change the organic matter morphology of soil, and among the present elements, Fe and Al mineral elements react most intensely during the freeze-thaw process; these reactions may consume oxygen and release carbon dioxide.…”
Section: Discussionsupporting
confidence: 92%
“…The increase in Al, Fe and Si atoms in the sediment particles means that these elements are released from the organic matter under the freeze-thaw action, and the increase in oxygen consumption during the release process leads to a decrease in the O atom content. This result confirms the hypothesis presented by Leanne et al [33] that freeze-thaw cycles change the organic matter morphology of soil, and among the present elements, Fe and Al mineral elements react most intensely during the freeze-thaw process; these reactions may consume oxygen and release carbon dioxide.…”
Section: Discussionsupporting
confidence: 92%
“…2), consistent with previous findings (Lyu et al, 2020;Wang et al, 2012). This is likely due to the great disparity in pH PZC (point of zero charge), which followed the order of Al oxyhydroxide (9.9; Figure S3) > Fe oxyhydroxide (7.2; Figure S3) > quartz sand (2-3) (Fisher-Power & Cheng, 2018). Furthermore, an increase in pH led to more negatively charged surface for both Fe/Al oxyhydroxide-coated and uncoated sand.…”
Section: Characteristics Of Psnp Suspension and Sandsupporting
confidence: 90%
“…Iron oxides (i.e., goethite and hematite) with concentrations from a few Ī¼g/L to several hundred mg/L are ubiquitously present in natural environment such as in soil and sediment . Since they can interact with different substances, iron oxides have been demonstrated to play important roles on the fate, transport, and cycling of nutrients or contaminants in soil and subsurface environments. āˆ’ For instance, many previous studies found that iron oxides could serve as mobile carrier for a wide of range of colloids such as dissolved organic matter, nanoscale titanium dioxide, bacteria, , and viruses, heavy metals such as lead, arsenic, and copper, , radioactive substances such as strontium and plutonium, and nutrients such as phosphorus , and sulfur . Hence, the fate and transport of iron oxides in porous media has drawn great attentions in past decades.…”
Section: Introductionmentioning
confidence: 99%